KOMPETENSI GURU DALAM MENYUSUN RPP MELALUI SUPERVISI AKADEMIK DI MADRASAH TSANAWIYAH: (Teacher Competence in Developing RPP through Academic Supervision in Madrasah) - Hasyim, Hasyim (Uniqbu Journal of Social Sciences, 2022)
This action research aims to scientifically prove whether continuous academic supervision can improve teacher competence in preparing lesson plans by referring to education role number. 22, the teacher’s book, the formulation of the question in this study is; does ongoing academic supervision improve teachers’ ability to prepare lesson plans? Negeri 1 Konawe? The method used in this action research is school action research. The results of the school action research indicated that; 1. Scientifically proven that continuous academic supervision improves teachers’ ability to prepare lesson plans at MTs 1 Tsanawiyah Negeri 1 Konawe. This is evidenced by an increase in the number of excellent faculty syllabuses from 31% to 83% after academic supervision. What’s more, the number of good quality lesson plans also increased from 31% to 89%; 2. The steps that lead to an increase in teacher competence in preparing the RPP include the following steps: a) Announcement of the supervision plan for teachers; b) Implementation of individual supervision, where each teacher is asked to present his RPP to the principal, then the principal provides input on the shortcomings of the teacher’s RPP; c) To check the originality of the lesson plans prepared by the teacher, the principal supervises the class. This fact, is done to adjust the plans included in the lesson plan and implement it in the classroom. If it is appropriate, it can be ascertained that the competence of the teacher in compiling the RPP is correct (not plagiarized or made by someone else). If there are a lot of discrepancies, it is likely that the RPP was produced by someone else; teachers were 52% and 58% more able to prepare lesson plans, respectively.